2006
DOI: 10.1097/01.inf.0000207403.67197.cc
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Epidemiology of Community-Acquired Methicillin-Resistant Staphylococcus aureus Infections Among Children With Risk Factors for Health Care-Associated Infection

Abstract: CA-MRSA strains recovered from children with RF-HAI were phenotypically similar to those recovered from healthy children The absence of SCCmec type II or III MRSA among children with RF-HAI suggests that CA-MRSA strains might have become endemic within pediatric health care facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
30
0
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 20 publications
6
30
0
7
Order By: Relevance
“…as infecciones osteo-articulares son una patología relativamente frecuente en pediatría, con una incidencia de 1: 1.000 a 1: 20.000 individuos para osteomielitis y 5,5 a 12: 100.000 para artritis séptica y comprenden tres entidades: artritis séptica, osteomielitis y la combinación de ambas [1][2] . La epidemiología de estas infecciones está cambiando, principalmente a causa de que Staphylococcus aureus resistente a meticilina de la comunidad (SARM-Co) es el agente más frecuente en algunos países de Latinoamérica como Argentina y Uruguay, por ejemplo [2][3][4][5][6] .…”
unclassified
See 1 more Smart Citation
“…as infecciones osteo-articulares son una patología relativamente frecuente en pediatría, con una incidencia de 1: 1.000 a 1: 20.000 individuos para osteomielitis y 5,5 a 12: 100.000 para artritis séptica y comprenden tres entidades: artritis séptica, osteomielitis y la combinación de ambas [1][2] . La epidemiología de estas infecciones está cambiando, principalmente a causa de que Staphylococcus aureus resistente a meticilina de la comunidad (SARM-Co) es el agente más frecuente en algunos países de Latinoamérica como Argentina y Uruguay, por ejemplo [2][3][4][5][6] .…”
unclassified
“…La epidemiología de estas infecciones está cambiando, principalmente a causa de que Staphylococcus aureus resistente a meticilina de la comunidad (SARM-Co) es el agente más frecuente en algunos países de Latinoamérica como Argentina y Uruguay, por ejemplo [2][3][4][5][6] . Aunque tradicionalmente considerado un patógeno nosocomial, SARM-Co se ha convertido ahora en una causa importante de infecciones en la comunidad, con pocos o ningún vínculo con centros de salud [2][3] . Su virulencia puede estar relacionada con su capacidad de producir toxinas, como la Panton-Valentine leucocidina (PVL), que tiene una capacidad única para destruir a los leucocitos, lo que resulta en la evasión bacteriana de la función bactericida de los mismos.…”
unclassified
“…Meticilinui 1960 m. patekus į rinką, jau po 6 mėnesių pasirodė pirmieji pranešimai apie atsparias padermes, kurios tapo vienomis dažniausių hospitalinių infekcijų sukėlėjų [6,7]. Nauji antimikrobiniai vaistai padeda tik trumpam suvaldyti šią problemą, greitai nustatoma ir jiems atsparių padermių, kurios peržengia ligoninės ribas.…”
Section: įVadasunclassified
“…Tokius ir panašius rizikos veiksnius tyrė ir kiti autoriai [22,31,33,34]. Jaunas amžius ir studijavimas nustatyti kaip statistiškai reikšmingi rizikos veiksniai S. aureus kolonizacijai [6,22,26,35]. Dar vienas teorija ir praktika 2016 -T. 22 (Nr.…”
Section: Rezultatų Aptarimasunclassified
“…In three Czech strains of S. aureus, the presence of lukS-PV a lukF-PV genes were determined by the National Reference Laboratory in the year 2004 and found to belong to CA-MRSA 56 . Antimicrobial resistance tests and selected methods of molecular biology demonstrated that their characteristics diff er from the multi-drug resistant HA-MRSA strains described in hospital patients 14,39,[57][58][59][60][61][62][63][64][65][66][67][68][69][70] .…”
Section: Current Knowledge Of Methicillin-resistant Staphylococcus Aumentioning
confidence: 99%